PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA KARYAWAN MELALUI PERILAKU KERJA - Ananda, Sunny Ratu; Arita, Sri (Universitas Bina Taruna Gorontalo, 2025)
This research explores the impact of transformational leadership and organizational citizenship behavior (OCB) on employee performance, with work behavior serving as a mediating factor, conducted at PT Anugerah Primarasa Bogatama (APB) Muara Bungo. A quantitative approach was applied using a survey of 90 active employees. Data analysis utilized Partial Least Square–Structural Equation Modeling (PLS-SEM) via SmartPLS. The findings indicate that both transformational leadership and OCB notably improve employee performance. Yet, only OCB significantly influences work behavior, whereas transformational leadership does not. Additionally, work behavior does not significantly mediate the relationship between transformational leadership, OCB, and performance. These results highlight the importance of inspirational leadership and proactive work conduct, yet also point to the necessity of strong organizational culture and support structures to maximize performance outcomes. The study enriches the understanding of behavioral mediation and offers strategic insights for leadership and HR development.